Corrigendum: Bioremediation of chromium (VI) by a microbial consortium isolated from tannery effluents and their potential industrial application - Bhattacharjee, Arghyadeep; Chaudhuri, Rajarshi; Pandey, Priyanshu; Mitra, Arup Kumar (Journal of Environmental Engineering and Landscape Management, 2022)
Arghyadeep Bhattacharjee, Rajarshi Chaudhuri, Priyanshu Pandey, Arup Kumar Mitra, authors of the article “Bioremediation of chromium (VI) by a microbial consortium isolated from tannery effluents and their potential industrial application”, published in Journal of Environmental Engineering and Landscape Management, 29(4), 418–429, https://doi.org/10.3846/jeelm.2021.15762 inform that 423 p. is a minor misinformation in the legend of Figure 4: Figure 4. Observation of Keratinase activity of the isolates. Graphical representation showing the amount of keratin activity by the microorganisms which were determined by the concentration of the vanillin degraded per ml of the crude enzyme. Y-axis indicates the enzymatic activity expressed in U/ml and X-axis denotes the test isolates. Data (n = 3) illustrated in the bar diagram as mean +SD. ***p < 0.0001 as determined by One-way ANOVA (IS1 to IS4 represents the isolates; BSA: Bovine Serum Albumin) The correct legend is: Figure 4. Observation of Keratinase activity of the isolates. Graphical representation showing the amount of keratin activity by the microorganisms. Y-axis indicates the enzymatic activity expressed in U/ml and X-axis denotes the test isolates. Data (n = 3) illustrated in the bar diagram as mean +SD. ***p < 0.0001 as determined by One-way ANOVA (IS1 to IS4 represents the isolates) The authors regret the error.